Analisis Pemilihan Warna Cat Dinding dengan Metode Data Mining Berdasarkan Kepribadian Pengguna - Supangat Supangat; Titasari Rahmawati (Komputika : Jurnal Sistem Komputer, 2022)
ABSTRACT – A personality test or so-called psychotest is an activity of measuring through a systematic stage to reveal certain psychological aspects of the individual. One of the most accurate personality tests is the MBTI (Myer Briggs Type Indicator). The results of the MBTI test can be used for consideration of various interests, such as work or for certain interests, for example to find out one's strengths and weaknesses, to build relationships with other people and other interests. The purpose of this study is to produce an application that can provide information about the paint color of the room that the pengguna chooses based on the pengguna's personality type that has been predetermined using the MBTI test. The information displayed is in the form of support and confidence values ​​for the relationship between the pengguna's personality type and favorite paint color. item. In addition, the application can also provide information in the form of data analysis on the personality type and color chosen by the pengguna using the FP-Growth (Frequent Pattern Growth) algorithm. The FP-Growth algorithm is a development of the Apriori algorithm with the aim of collecting data that appears at the same time then grouping and creating a list of items that often appear. In determining the percentage results of support and confidence carried out by the system, it depends on the amount of data and the minimum amount of support that is input. More data will affect the percentage result and will speed up the analysis process using FP-Growth. By analyzing the results of frequent itemset, a rule can be formed that can be used by pengguna references in selecting or combining wall paint colors based on the pengguna's personality.